Cutaneous Invasive Aspergillosis: Retrospective Multicenter Study of the French Invasive-Aspergillosis Registry and Literature Review. Issue 26 (July 2015) - Bernardeschi, Céline; Foulet, Francoise; Ingen-Housz-Oro, Saskia; Ortonne, Nicolas; Sitbon, Karine; Quereux, Gaëlle; Lortholary, Olivier; Chosidow, Olivier; Bretagne, Stéphane
Abstract : Abstract: Invasive aspergillosis (IA) has poor prognosis in immunocompromised patients. Skin manifestations, when present, should contribute to an early diagnosis. The authors aimed to provide prevalence data and a clinical and histologic description of cutaneous manifestations of primary cutaneous IA (PCIA) and secondary CIA (SCIA) in a unique clinical series of IA and present the results of an exhaustive literature review of CIA. Cases of proven and probable IA with cutaneous manifestations were retrospectively extracted from those registered between 2005 and 2010 in a prospective multicenter aspergillosis database held by the National Reference Center for Invasive Mycoses and Antifungals, Pasteur Institute, France. Patients were classified as having PCIA (i.e., CIA without extracutaneous manifestations) or SCIA (i.e., disseminated IA). Among the 1, 410 patients with proven or probable IA, 15 had CIA (1.06%), 5 PCIA, and 10 SCIA. Hematological malignancies were the main underlying condition (12/15). Patients with PCIA presented infiltrated and/or suppurative lesions of various localizations not related to a catheter site (4/5), whereas SCIA was mainly characterized by disseminated papules and nodules but sometimes isolated nodules or cellulitis. Histologic data were available for 11 patients, and for 9, similar for PCIA and SCIA, showed a dense dermal polymorphic inflammatory infiltrate, with the epidermis altered in PCIA only. Periodic acid Schiff and Gomori-Grocott methenamine silver nitrate staining for all but 2 biopsies revealed hyphae compatible with Aspergillus . Aspergillus flavus was isolated in all cases of PCIA, with Aspergillus fumigatus being the most frequent species (6/10) in SCIA. Two out 5 PCIA cases were treated surgically. The 3-month survival rate was 100% and 30% for PCIA and SCIA, respectively. Our study is the largest adult series of CIA and provides complete clinical and histologic data for the disease. Primary cutaneous IA should be recognized early, and cases of extensive necrosis should be treated surgically; its prognosis markedly differs from that for SCIA. Any suppurative, necrotic, papulonodular, or infiltrated skin lesion in an immunocompromised patient should lead to immediate biopsy for histologic analysis and mycological skin direct examination and culture.